Novel imprinted polyethyleneimine nano-fluorescent probes with controllable selectivity for recognizing and adsorbing metal ions. Issue 57 (20th July 2017) - Jia, Jin; Cheng, Gui-Juan; Wu, Aihua; Luan, Shengji
Abstract : Novel ion imprinted nano-fluorescent probes based on polyethyleneimine (PEI) were obtained via simple imprinting and grafting with fluorescein, and used for high recognition, detection and adsorption of Cu 2+, Zn 2+ and Cr 3+ in aqueous solution. Abstract : Novel ion imprinted nano-fluorescent probes (IIP–fluorescein) based on polyethyleneimine (PEI) were obtained via simple imprinting and grafting with fluorescein, and used for high recognition, detection and adsorption of Cu 2+, Zn 2+ and Cr 3+ in aqueous solution. The selectivity of PEI is adjustable through an imprinting process for Cu 2+, Zn 2+ or Cr 3+, which have a strong affinity for the amino group. Each probe reveals specific selectivity to and recognition of the relevant template metal ion over seven other common metal ions. The three probes exhibit a large linear detection range, high accuracy and strong adsorption capacity for Cu 2+, Zn 2+ and Cr 3+ . The sensitive and selective detection, as well as the removal of Cu 2+, Zn 2+ and Cr 3+ by using IIP–fluorescein was further demonstrated in polluted tap and river water, indicating their potential application in environmental monitoring and treatment. Additionally, the sensing mechanism of IIP–fluorescein for metal ions was investigated through Gaussian 09. The synergistic effect of photo-induced electron transfer (PET) and intramolecular charge transfer (ICT) was demonstrated in the sensing process for metal ions. The design concept might propose a method for developing and studying other fluorescent probes with similar systems (containing amino groups, mercapto groups or cyano groups).